The effect of education on migration: evidence from school reform - Petri Böckerman; Mika Haapanen (European Regional Science Association (ERSA), 2010)
In the 1990s polytechnic education reform took place in Finland, which gradually expanded higher education to all Finnish regions; the polytechnics constituted a new non-university sector in higher education. This reform is used to study the causal effect of education on the inter-regional migration. First we consider the impact of the reform on the migration of graduating high school students, followed by an investigation of school-to-work migration. Instrumental variables estimators are implemented that exploit the exogenous variation in the local supply of polytechnic education. Large panel micro-data are used.
Keywords: J10; J61; I20; R23; 330; migration; higher education; polytechnic reform; IV estimation